Infrared, X-Ray Diffraction Studies and Thermogravimetric Behaviour of Magnesium Myristate and Magnesium Palmitate - Singh, Chitra; Upadhyaya, S.K. (Asian Journal of Chemistry, 2011)
Magnesium soaps i.e., magnesium myristate and magnesium palmitate were prepared by the metathesis of potassium soaps with an aqueous solution of magnesium sulphate. The infrared results showed that the fatty acid exists in a dimeric structure as a result of hydrogen bonding between the carboxyl groups of two acid molecules, whereas magnesium soaps have an ionic character. The X-ray diffraction analysis indicates that the zig-zag chains of fatty acid radical constituent of the soap molecules extend straight forward on both sides of each basal plane. The thermal decomposition of these soaps was found kinetically of zero order and energy of activation for the decomposition process was in the range of 15-32 KJ mol-1.